Climatic characterization of forest zones across administrative boundaries improves conservation planning. Issue 2 (21st October 2014) - Klassen, Heather A.; Burton, Philip J.; Goslee, Sarah
Abstract Aim This paper demonstrates methods to extend standardized vegetation zone descriptions and mapped distributions across political boundaries. An extended climate niche for North America's Coastal Douglas‐fir (CDF) forest zone is determined and projected to evaluate its potential distribution under a changing climate and to identify climate refugia for conservation planning. Location Pacific Northwest temperate rain forest in British Columbia (BC), CA, and nearby Washington (WA) and Oregon (OR), US. Methods Using a combination of ecosystem polygon mapping and ecological plot data with climate interpolation tools, forests characterized as CDF under BC's biogeoclimatic ecosystem classification system were identified in the neighbouring US. Current (baseline) limits to CDF distribution were identified and used to map its potential distribution and climate refugia under future climate conditions using ensemble Global Climate Model projections. Results The extended CDF climate niche covers 76 725 km2 under baseline conditions, with the majority of the area in the Pacific Northwest US. The extended CDF forest zone includes a vegetation assemblage consistent with existing definitions of BC's CDF moist maritime subzone, but also an additional vegetation assemblage representing a drier maritime subzone. Projections of future climate suggest a northerly shift (~150 km) and a decrease (−91.5%) in overall CDF area. Climate refugia are projected for discontinuous patches of CDF forest on Vancouver Island and adjacent mainland. Conclusions This project combined georeferenced ecological plot data and digital maps, thereby facilitating the international mapping of ecosystem distributions in adjacent administrative areas that do not currently use the same ecosystem classification and mapping systems. This approach and the concept of climate niche definition, distribution and persistence are applicable to the management, restoration and conservation of plant communities, particularly in evaluating future ecosystem range shifts and disruptions associated with a changing climate. The potential for dramatic reductions in the range of the Coastal Douglas‐fir zone, with persistence in <15% of its current area, suggest that most of the extended CDF zone is marginally suitable for the characteristic CDF ecosystems and that slight shifts in climate or disturbance regime may greatly alter the character of the vegetation. The full climatic niche for British Columbia's Coastal Douglas‐fir forest zone is determined from its mapped distribution and georeferenced plot data in the neighbouring USA. A new subzone is characterized, and the potential distribution of the extended zone is projected under a changing climate to identify climate refugia. For sensitive ecosystems with multi‐jurisdictional distributions, this approach helps focus conservation efforts.